2007
DOI: 10.1113/jphysiol.2007.141572
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxygen in prenatal growth: studies in the chick embryo

Abstract: The compelling evidence linking small size at birth with later cardiovascular disease has renewed and amplified scientific and clinical interests into the determinants of fetal growth. It is accepted that genes and nutrition control fetal growth; however, prior to this study, it had been impossible to isolate the effect of increases and decreases in fetal oxygenation on the regulation of prenatal growth. We investigated the role of oxygen in the control of fetal growth in the chicken because in contrast to mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 26 publications
5
105
0
4
Order By: Relevance
“…Some experimental studies of growth under manipulated O 2 are consistent with the WBE expectations; exposure to chronic hypoxia results in a decrease in adult size in some insects (Klok and Harrison 2009;Harrison et al 2010) as well as reduced growth rates in fish (Wang et al 2009), American alligators Alligator mississippiensis (Owerkowicz et al 2009), and embryonic mammals and birds (de Grauw et al 1986;Giussani et al 2007). For many species, processes like growth respond to hypoxia in a threshold manner and only under extreme conditions (Chabot and Dutil 1999;McNatt and Rice 2004).…”
Section: Testing Growth Models I: Changing Environmentssupporting
confidence: 53%
“…Some experimental studies of growth under manipulated O 2 are consistent with the WBE expectations; exposure to chronic hypoxia results in a decrease in adult size in some insects (Klok and Harrison 2009;Harrison et al 2010) as well as reduced growth rates in fish (Wang et al 2009), American alligators Alligator mississippiensis (Owerkowicz et al 2009), and embryonic mammals and birds (de Grauw et al 1986;Giussani et al 2007). For many species, processes like growth respond to hypoxia in a threshold manner and only under extreme conditions (Chabot and Dutil 1999;McNatt and Rice 2004).…”
Section: Testing Growth Models I: Changing Environmentssupporting
confidence: 53%
“…Animal models of maternal hypoxia recapitulate these findings, demonstrating that IUGR can result from maternal hypoxia (95,96) . Giussani et al initially, using a chick embryo model (97) and subsequently a rat model (98) demonstrated that this IUGR was due to the hypoxia per se, and not maternal malnutrition, as severe hypoxia can result in reduced maternal food intake. Maternal hypoxia has also been shown to programme cardiac dysfunction in these rat and chick embryo models (99,100) , including promotion of fetal cardiac overload, leading to ventricular and aortic wall thickening (101) and endothelial dysfunction (102) .…”
Section: Maternal Hypoxiamentioning
confidence: 99%
“…Of note, multigenerational highaltitude populations demonstrate protection against the effects of high-altitude hypoxia on fetal growth (14)(15)(16)(17)(18). Experimental studies in animal models support the likelihood that prenatal hypoxia can program cardiac, vascular, and metabolic dysfunction in the adult offspring (19)(20)(21), and that high-altitude ancestry protects against the effect of chronic hypoxic development on fetal growth (22).…”
mentioning
confidence: 99%